(untitled) (Experimental biology, 2015)
In the current article we have shown the current state of species and genetic biodiversity, the role of biodiversity and possibilities of its use in the Republic of Kazakhstan. Moreover, the information about rare and extinct fl ora and fauna species has been presented. The main threats to the disappearance of fl ora and fauna species and the barriers to the protection and effective management of biodiversity, which occur on systematic, institutional and individual levels, are shown. The actual tasks for biodiversity protection are defi ned. The analysis of the actual and effective steps in the fi eld of biodiversity protection has been done in our country.